Construtos de experiência de limiar no cinema - Pires, Rumenig Eduardo Pereira (Universidade do Vale do Rio dos Sinos, 2018)
The main purpose of the dissertation is to analyze how films construct threshold experiences. The corpus consists of films that have embedded narratives that engender worlds, between which there is a limited threshold. Starting from this general objective, the text is structured on two research axes: first, it focuses on how the characters experience threshold experiences within the filmic construct, trying to understand how these constructs are realized technically, aesthetically and narratively; a second, identifies analogies between the experience lived by the characters in the film’s fictional world and the liminal experiences lived by the spectator in the everyday world, promoting a reflection on how such constructs enable the refiguration of spectator's own relationship with cinema. Out of cartographies of the films’ contrasting worlds and constellations of threshold experience constructs, the analysis led to the conclusion that the construct in question is a virtuality actualized in the films at three levels: material, diegetic, and analogical. The corpus consists of Titanic (CAMERON, 1997), Avatar (CAMERON, 2009), The Great Gatsby (LUHRMANN, 2013) and La La Land (CHAZELLE, 2017). The main authors worked with are Henri Bergson, Walter Benjamin, Hans Gumbrecht, Vilém Flusser, Bordwell and Thompson, Inês Gil, Kendall Walton, and Paul Ricoeur.
Keywords: Comunicação; Cinema; Limiar; Mundos contrastantes; Communication; Cinema; Threshold; Contrasting worlds; ACCNPQ::Ciências Sociais Aplicadas::Comunicação